Web based systems security review and trends - Mwiti, Jackson (Meru: Meru University of Science and Technology, 2022)
Security of any web application is paramount because any breach to this can result to major consequences. Many developers have given web security an afterthought which has made it possible for the attackers to target these systems. Technology has also contributed to security vulnerability since most applications were built on old platforms which make it harder to be compatible. Cyber wars among the countries and many other more reasons have worsened the situation. Emergent of artificial intelligent has given hope to the fight gain some of the security threat. The main objective of this paper is to review on the current trend of web based systems security. The paper has applied exploratory research design to review on security of web applications, protection mechanism and the role of convolution neural networks. The outcome of this review aims on improving the body of knowledge.